Minvisited: A Message Routing Protocol for Delay Tolerant Network - Marin-Caihuan, J; Veas-Castillo, L; Ovando-Leon, J (Institute of Electrical and Electronics Engineers Inc., 2018)
We studied routing protocols for Delay Tolerant Networks devised to improve the message delivery performance in natural disaster scenarios. In this paper we propose the MinVisited protocol which during the transitive path to the message destination, selects the next node based on two features: (1) the most distant neighbor, and (2) the largest number of encounters with the destination node of the message. We compare our protocol with well-known protocols of the technical literature. The results show that the proposed protocol presents a low workload overhead with a number of hops lower than 2, and in average 95% of the messages are successfully delivered. © 2018 IEEE.